2021
DOI: 10.1021/acsestwater.0c00207
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–Clay Composites for Wastewater Treatment: A State-of-the-Art Review

Abstract: In recent decades, increased domestic and industrial activities have led to the release of various pollutants into the aquatic environment. A robust and eco-friendly technique for removing these pollutants from wastewater is a crucial need. Among existing technologies, adsorption is considered to be a simple, cost-effective, and sustainable method. Recently, chitosan−clay nanocomposites have emerged because of their high abundance, ease of fabrication, and efficacy as adsorbents. Quantitatively, this particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 254 publications
0
24
0
Order By: Relevance
“…The majority of these technologies produce minimal industrial impacts, since they are time-consuming, costly, and result in secondary pollutants. Adsorption is one of the most efficient and extensively employed technologies for wastewater treatment due to the utilization of widely accessible by-products and inexpensive substitutes, including bio-wastes, fly ash, chitosan [ 78 ], and chitin. Additionally, adsorption involves the application of nanostructures for the extraction of these toxic substances from water bodies.…”
Section: Nanomaterials Used For Heavy Metal Removalmentioning
confidence: 99%
“…The majority of these technologies produce minimal industrial impacts, since they are time-consuming, costly, and result in secondary pollutants. Adsorption is one of the most efficient and extensively employed technologies for wastewater treatment due to the utilization of widely accessible by-products and inexpensive substitutes, including bio-wastes, fly ash, chitosan [ 78 ], and chitin. Additionally, adsorption involves the application of nanostructures for the extraction of these toxic substances from water bodies.…”
Section: Nanomaterials Used For Heavy Metal Removalmentioning
confidence: 99%
“…Because of the renewability, biodegradability, nontoxicity, biocompatibility, and functionality, biopolymers have attracted more research attention in the recent decade for applications in many fields, including agriculture, food, , cosmetics, biomedicine, , electronics, building, , and environmental remediation. Chitosan, a poly-β-glucosamine biopolymer produced by alkaline deacetylation of chitin derivatives found in the exoskeleton of arthropods, , has been widely studied for its application in water treatment and contaminant removal. Various studies have shown that chitosan exhibits excellent performance in removing cationic heavy metals, e.g., Pb­(II), , oxoanionic heavy metals, e.g., As, and dyes and organic contaminants . However, chitosan as an adsorbent has major drawbacks, including a low porosity and a small surface area, low acid stability and thermal stability, poor mechanical properties, and hydrophilicity. , As a result, chitosan is often used in composites with inorganics or modified with other materials to address the various deficiencies to produce a robust adsorbent. ,, …”
Section: Introductionmentioning
confidence: 99%
“…20,23 As a result, chitosan is often used in composites with inorganics or modified with other materials to address the various deficiencies to produce a robust adsorbent. 17,23,24 Alkali-activated materials such as geopolymers or poly-sialate inorganic polymers are low-cost materials known to also exhibit excellent performance in removing and immobilizing aqueous heavy metal ions. 25−28 These classes of materials are prepared by reacting aluminosilicate precursors such as fly ash, slag, or calcined clay with alkaline activating solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides being biodegradable, they are biocompatible 2 and many of the biopolymers possess significant antibacterial activity. 3 As a result, these are preferred by the researchers over conventional synthetic polymers for various applications in food, 4 cosmetics, 5 commercial manufacturing goods, 6 pharmaceutical and medical products, [7][8][9] drug development, 10,11 nanofiber fabrication, 12 wastewater treatment, [13][14][15][16] energy storage devices, 17 etc. However, these applications demand a biopolymer of specific physical properties extracted via a simple pathway using fewer toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%